Edible crickets (Orthoptera) around the world: distribution, nutritional value, and other benefits - a review - Magara, H.J.; Niassy, S.; Ayieko, M.A.; Mukundamago, M.; Egonyu, J.P.; Tanga, C.M.; Kimathi, E.K.; Ongere, J.O.; Fiaboe, K.; Hugel, S.; Orinda, M.A.; Roos, N.; et al. (Frontiers Media, 2021)
Edible crickets are among the praised insects that are gaining recognition as human food and livestock feed with a potential of contributing to food security and reduction of malnutrition. Globally, the sustainable use of crickets as food or feed is undermined by lack of information on the number of the edible crickets, the country where they are consumed, and the developmental stages consumed. Furthermore, lack of data on their nutritional content and the potential risks to potential consumers limits their consumption or inclusion into other food sources. We reviewed published literature on edible cricket species, countries where they are consumed, and the stage at which they are consumed. We further reviewed information on their nutritional content, the safety of cricket consumption, and the sensory qualities of the edible crickets. We also looked at other benefits derived from the crickets, which include ethnomedicine, livestock feed, pest management strategies, contribution to economic development, and livelihood improvement, particularly in terms of use as food preservatives and use within music, sports, and cultural entomology. Lastly, we reviewed information on the farming of edible crickets. In this review, we report over 60 cricket species that are consumed in 49 countries globally. Nutritionally, crickets are reported to be rich in proteins, ranging from 55 to 73%, and lipids, which range from 4.30 to 33.44% of dry matter. The reported amount of polyunsaturated fatty acids (PUFA) is 58% of the total fatty acids. Edible crickets contain an appreciable amount of macro- and micro-mineral elements such as calcium, potassium, magnesium, phosphorus, sodium, iron, zinc, manganese, and copper. Also, the crickets are rich in the required amount of vitamins such as B group vitamins and vitamins A, C, D, E, and K. Overall, the cricket species examined in this review are safe to be consumed, and they display high proximate content that can replace plant and livestock products. The crickets play valuable roles in contributing to the economies of many countries and livelihoods, and they have medicinal and social benefits. This review is expected to promote greater recognition of crickets as a source of food, feed, and other benefits in the world and encourage up-scaling by farming them for sustainable utilization.